Triolimus: A Multi-Drug Loaded Polymeric Micelle Containing Paclitaxel, 17-AAG, and Rapamycin as a Novel Radiosensitizer - Tomoda, Keishiro (Macromol Biosci, 2016)
Triolimus is a multi-drug loaded polymeric micelle containing paclitaxel (PTX), 17-allylamino-17-demethoxygeldanamycin (17-AAG), and rapamycin (RAP). In this study, we examined the radiosensitizing effect of Triolimus in vitro and in vivo. Radiosensitizing effects of Triolimus on A549 cells were dose dependent and at 2 nM, Triolimus showed significant radiosensitization even at low radiation doses (2 Gy). By sensitivity enhancement ratio (SER), PTX alone, dual drug combinations, and Triolimus treatment at 2 nM had radiosensitizing effects with potency as follows: PTX alone (PTX) > PTX and RAP (P/R) > Triolimus (TRIO) > PTX and 17-AAG (P/17) > 17-AAG and RAP (17/R). In vivo, fractionated radiation of 15 Gy preceded by infusion of PTX alone, dual drug combinations, or an intermediate dose of Triolimus (Int. TRIO: PTX/17-AAG/RAP at 15/15/7.5 mg/kg) strongly inhibited A549 tumor growth. Notably, pretreatment with high dose of Triolimus (High TRIO: PTX/17-AAG/RAP at 60/60/30 mg/kg) before the fractionated radiation led to tumor control for up to 24 weeks. An enhanced radiosensitizing effect was observed without an increase in acute toxicity compared to PTX alone or radiation alone. These results suggest that further investigations of Triolimus in combination with radiation therapy are merited.